Margaret Atwood's MaddAddam and Finding a Postpandemic Kinship in the COVID-19 Era. Issue 1 (1st April 2022) - Fetherston, Rachel
Abstract : The COVID-19 pandemic has revealed much about intrahuman relations, exposing a "politics of pandemic othering" through its exacerbation of pre-existing social and political tensions while unsettling previously accepted understandings of sickness, care, and communal obligation. Just as significantly, the pandemic has also underlined the complex connections that exist between humans and nonhumans—both in the context of human-virus relations, and in the broader context of anthropogenic devastation of the natural world. This paper presents an analysis of Margaret Atwood's MaddAddam (2013), as read alongside the events of the COVID-19 pandemic, as an "ecosickness" narrative that considers the impact of a human-induced viral apocalypse on human-nonhuman relations. In particular, the novel explores the possibility of developing more positive, meaningful relationships with more-than-human others in the wake of a viral pandemic. Utilizing Donna Haraway's thoughts on "kin-making" and Heather Houser's work on "ecosickness fiction, " I argue that the interconnectedness depicted between humans and nonhumans in MaddAddam represents the potential to develop what I term a "postpandemic kinship" in the COVID-19 era. I explore how the narrative of MaddAddam is generally positioned to explore this idea of human-nonhuman kinship and then discuss this further in relation to three key motifs that appear throughout the text: the nonhuman animal, refugia, and stories and storytellers.